Identifikasi Habituasi Literasi pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - Marlin, Marlin; Rahmah, Nur; Mirnawati, Mirnawati (South Sulawesi Education Development, 2024)
This study aims to identify the habituation of reading and writing literacy in elementary schools, focusing on the implementation process, challenges, and solutions. The research is qualitative in nature, employing a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. Data analysis follows the interactive analysis technique based on the theory of Miles and Huberman. The subjects of this research are fifth-grade students and their homeroom teachers at SD 46 Matarin, Bastem District. Findings reveal that the implementation of reading and writing literacy habituation in Indonesian language learning at the elementary level aligns with the guidelines set by the Ministry of Education, Culture, Research, and Technology. The obstacles encountered include students' lack of interest in reading and concentration, insufficient support from the family environment, and limited facilities and resources. Solutions proposed include providing a variety of reading materials, engaging parents, and personalized approaches by teachers to students.